Dilution of Seawater Affects the Ca2 + Transport in the Outer Mantle Epithelium of Crassostrea gigas - Sillanpää, J. Kirsikka; Cardoso, Joao Carlos dos Reis; Félix, Rute Castelo; Anjos, Liliana; Power, Deborah Mary; Sundell, Kristina (Frontiers in Physiology, 2020)
A modified salinity of coastal waters due to climate change is likely to affect the physiology and ion transport capabilities of calcifying marine organisms such as bivalves. To investigate the physiological effect of decreased environmental salinity in bivalves, adult oysters (Crassostrea gigas) were exposed for 14 days to 50% seawater (SW, 16 ppt) and the effects on mantle ion transport, electrophysiology and the expression of Ca2+ transporters and channels relative to animals in full strength sea water was evaluated. Exposure of oysters to 50% SW decreased the active mantle transepithelial ion transport and specifically affected Ca2+ transfer. Gene expression of the Na+/K+ -ATPase and the sarco(endo)plasmic reticulum Ca2+-ATPase was decreased whereas the expression of T-type voltage-gated Ca channel and Na+/Ca2+ –exchanger increased compared to animals maintained in SW. The results indicate that decreased environmental salinities will most likely affect not only osmoregulation but also bivalve calcification and shell formation.